Compostos de Pd(II) contendo ligantes N,S-doadores: síntese, caracterização e estudo da atividade citotóxica - Moura, Thales Reggiani de [UNESP] (2016)
In the last years, the interest of new drugs based on metals in order to treat cancers has been increasing considerably. The discovery of cisplatin antitumor activity and its subsequent success as a cancer treatment drug has inspired the study of several analogous compounds, which presented, in general, similar patterns of antitumor activity and susceptibility to resistance. By presenting the same electronic configuration and geometry of Pt(II) complexes, coordination complex containing Pd (II) ion have been extensively studied, and recognized different activity patterns for these compounds containing ligands N,S-donor in relation to compounds of Pt (II). In this work, were synthesized and characterized four novel complexes of palladium(II) type [PdX(tedmPz')(PPh3)] {tedmPz' = N-ethyl-1-iminothiolate-3,5-dimethylpyrazole; X = Cl-, Br-, I-, SCN-; PPh3 = triphenylphosphine}. The complexes were characterized by vibrational spectroscopy techniques in the IV region and 1H NMR and 13C NMR, elemental analysis, mass spectrometry ESI / MS and X-ray diffraction of single crystal, indicating a square planar environment around the metal with its sites coordination occupied by triphenylphosphine, the N,S-anionic coordination of tedmPz ligand, the N-terminal coordination mode of thiocyanate. It is also described the synthesis and spectroscopic characterization in the IV region and 1H NMR and 13C for the tedmPz compound. The in vitro cytotoxicity of the ligand and all of the complexes were evaluated by the MTT method, against the cell cultures of murine tumors MCF-7 (human breast adenocarcinoma). All compounds had their ability to interact with a nucleoside (guanosine) investigated with the objective of evaluating their possible covalent interaction with DNA. The results indicated that the variation of halide ligands did not affect the cytotoxicity of the complexes and the synthesized compounds showed no ability to interact with guanosine, which is a preliminary evidence that covalent interaction between the synthesized compounds and the DNA is not the main source of cytotoxicity of these. It is noteworthy that all the compounds were more cytotoxic than cisplatin, obtaining an average of IC50 values of up to 2.4 times lower than the comparison drug.